2012
DOI: 10.2351/1.4730804
|View full text |Cite
|
Sign up to set email alerts
|

Nano structures via laser interference patterning for guided cell growth of neuronal cells

Abstract: Laser interference patterning is a versatile tool for the fabrication of nano patterns. For this study, regular nano line patterns with feature sizes between 100 and 1000 nm were produced on polymers polyimide, polyetheretherketone, and polydimethylsiloxane. Cell culture experiments with B35 neuronal cells revealed the alignment of cellular extensions along nano grooves of different feature sizes. Especially, when feature depth exceeds a distinct threshold (aspect ratio > 0.6), more than 50% of cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…In vitro results, showed a better cell alignment for patterns formed with lines separated distances below 50 µm. Bremus-Koebberling et al [45] followed a similar approach, but using nano-grooves. They evaluated the influence of linear-like nanopatterns produced by laser interference patterning (λ = 355 nm, pulse duration = 38 ns) on the cell alignment using B35 neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro results, showed a better cell alignment for patterns formed with lines separated distances below 50 µm. Bremus-Koebberling et al [45] followed a similar approach, but using nano-grooves. They evaluated the influence of linear-like nanopatterns produced by laser interference patterning (λ = 355 nm, pulse duration = 38 ns) on the cell alignment using B35 neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] Researchers have been working on micro-or nanopatterned substrates to guide neuronal outgrowth, to help study the neural electrical signal transmission in single neurons, 5 and to aid nerve regeneration processes. 6 Therefore, our goal is to combine microfluidics with tissue engineering to create a "living brain," generating realistic in vitro neural circuitry, which can be used to standardize experimental neuronal cell culture. 7 Networks of neurons cultured on-chip can provide insights into both normal and disease-state brain function.…”
Section: Introductionmentioning
confidence: 99%
“…20 Bremus-Koebberling et al proposed a conduit with various combinational patterns of groove width and depth and reported that different width and depth combinations had different guiding capabilities. 21 Bechara and Popat observed the attachment and growth of neural progenitor cells on a scaffold with micropatterns and nanowires. Their experimental results indicated that micro/ nanohybrid structures could affect the morphology of cells and promote cell differentiation.…”
Section: Introductionmentioning
confidence: 99%